CFD analysis of temperature imbalance in superheater/reheater region of tangentially coal-fired boiler - Zainudin A.F.; Hasini H.; Fadhil S.S.A. (Institute of Physics Publishing, 2023)
Coal fired boilers; Computational fluid dynamics; Engineering research; Fossil fuel power plants; Superheaters; CFD analysis; Cross sectional area; Flue gas temperatures; Gain insight; Imbalance problem; Steam temperature; Tube leaks; Velocity deviation; Boilers